A Randomized Control Trial to Assess the Efficacy of Calcium Alginate Dressing Versus Conventional Gauze Dressing on Bacterial Load in Infected Diabetic Foot Ulcer - Devendra D. Jalde1, Satyajit A. Godhi1, Metgud S.C2, A.S. Godhi, Pandey Rakesh Kumar1*, Metgud S.C1, (Recent Research in Science and Technology, 2011)
Diabetic foot ulcers are common and estimated to affect 15% of all diabetic individual during their lifetime. Infection is one of the major cause for non-healing of the ulcer in diabetes. Objectives of present study were to measure the effect of calcium alginate dressing on bacterial load in infected diabetic foot ulcer in comparison to conventional gauze dressing. Present one year randomized controlled trial was conducted in Department of Surgery, KLES Dr. Prabhakar Kore Hospital and Medical Research Centre, Belgaum on 60 patients with infected diabetic foot ulcer during period of January 2008 to December 2008. Patients were divided into two different groups by number randomization (Group 1 Calcium alginate and Group 2 conventional gauze). Bacterial load was determined per gram of tissue before first and after third dressing in both groups. In the present study male preponderance was seen. The duration of DM was 6 to 10 years in majority of the patients. The mean bacterial load (X 105 CFU/gm tissue) before the first dressing in calcium alginate group was 513.3±122.4 while in conventional gauze group it was 516.7±117.7 and after the third dressing was 526.7±138.8 and 536.7±121.7 respectively. There was increase in bacterial load after the three dressings over the diabetic foot ulcer in both the groups. However this increase was not statistically significant (p=0.787). Present study has shown that dressing with calcium alginate is ineffective in reducing bacterial load of infected diabetic foot ulcers.